Software quality metrics aggregation - Dasso, Aristides (2012)
Evaluating Software Quality is a critical and very important aspect of software development. There are several metrics developed to assess different characteristics of a software system so as to evaluate its overall quality. One international standard for Software Quality is the ISO/IEC 9126 International Standard; this standard is “proposed to make sure the ‘quality of all software-intensive products’ including safety-critical systems where lives will be at jeopardy if software components fail to succeed.” However, there is no provision to integrate/aggregate different metrics into one value allowing the developer to comprehend rapidly the quality of a software product without having to refer to several different metrics. We propose in this work a way to aggregate different metrics into a single value using a Continuous Logic –the one proposed in Logic Score of Preference (LSP) method.